PELAYANAN KESEHATAN PRIMER SEBAGAI GATEKEEPER DAN KEBIJAKAN DISKUSI PEER REVIEW: ANTARA KUALITAS DAN REALITAS UNTUK MENURUNKAN KASUS RUJUKAN NON SPESIALISTIK - Zahrina, Zahrina; Ramadani, Royasia Viki; Hulwah, Khairun Nisa il; Nurlatifah, Siti; Andalan, Aldi; Gani, Ascobat; Kurniawaty, Golda; Setiawan, Ery (UI Scholars Hub, 2023)
Almost 80% of the source of funds is spent on hospital. This situation indicates the failure of the gatekeeper function in primary health care. Performance-based capitation is implemented to ensure the cost and quality of primary care, with non-specialist referral rate as one of the particular parameters. The peer review policy is a discussion between BPJS Health, District/City Health Services, IDI, provincial and branch Team of KMKB and other relevant stakeholders to determine which diagnoses must be handled at FKTP also to accommodate and improve the capacity of FKTP to handle patients and minimize referral cases. This study aims to evaluate the implementation of peer review discussions and analyze the obstacles, challenges and potential of peer review policies to optimize the FKTP gatekeeper function. The research method is qualitative, and it involves conducting in-depth interviews, FGDs, and literature reviews. In general, the peer review policy is quite good in controlling referral cases, especially RNS (Non-Specialist Referrals). In general, the peer review policy is entirely reasonable to control referral cases, especially RNS. Evaluation of the